DEMO DAY SEBAGAI TOMBAK KEBERHASILAN PROGRAM. ANALISIS PENGARUH PROGRAM WIRAUSAHA MERDEKA TERHADAP PERKEMBANGAN MOCHABBY DI UNTAG SURABYA - Regina Ayu Prasanthi; Ni Made Ida Pratiwi (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The Independent Entrepreneurship Program is a program from the Indonesian Ministry of Education, Culture, Research, and Technology which is part of the Independent Campus program. It aims to provide opportunities for students to learn to develop themselves into prospective entrepreneurs through activities outside of class. The Independent Entrepreneurship Program collaborates with the Implementing Universities. This study will discuss the influence of the Independent Entrepreneurship program on the development of Mochabby at the University of 17 August 1945 Surabaya. Mochabby is a non-alcoholic beverage innovation that combines classic mojito elements with the addition of fresh fruit flavors, creating a unique and refreshing taste sensation. In recent years, more and more people have been looking for healthy and refreshing alternative drinks without alcohol content. This study uses a descriptive approach to analyze the influence of this program on various aspects of the business, such as marketing strategies, financial management, and increasing sales. This study uses a descriptive method with a qualitative and quantitative approach. Data were collected through observation, interviews, consumer surveys, and financial analysis. The results of the study show that WMK makes a significant contribution to various aspects of business development, including increasing brand awareness, product innovation, product diversification, better financial management, and expanding marketing networks.